Molecular Characterization and Antibiotic Susceptibility Pattern of Coagulase-Negative Staphylococci (Cons) Isolated from Clinical Samples in A Tertiary Care Hospital, Kathmandu, Nepal - Pradeep Kumar Shah; Niru Bhandari; Rajendra D. Joshi (The Bioscan, 2024)
Coagulase-negative staphylococci (CoNS), once considered non-pathogenic skin commensals, have emerged as significant opportunistic pathogens in healthcare settings. This study investigates the phenotypic and genotypic characteristics of CoNS isolated from clinical samples in a tertiary care hospital in Kathmandu, Nepal. A total of 3,690 clinical specimens were processed, yielding 113 CoNS isolates identified through biochemical tests and sugar fermentation profiles. Species-level identification revealed S. epidermidis (45.1%) as the most prevalent species, followed by S. saprophyticus (23.9%) and S. haemolyticus (16.8%). Antibiotic susceptibility testing indicated 98.2% sensitivity to Linezolid and 100% resistance to Ampicillin. Biofilm formation was observed in 35.4% of isolates, predominantly in S. epidermidis. Genotypic analysis using 16S rRNA sequencing confirmed species identification and revealed significant genetic diversity. These findings highlight the need for species-level identification and tailored antimicrobial therapies to manage CoNS infections effectively.